An Outline of Worldwide Barriers in Science, Technology, Engineering and Mathematics (STEM) Education (Jurnal Pendidikan IPA Indonesia, 2019)
This study aimed to identify and classify the barriers in Science, Technology, Engineering, and Mathematics (STEM) Education around the world. The barriers have been investigated in the intrinsic, extrinsic, and institutional domains by reviewing the literature and related works. In STEM education, the intrinsic barrier focuses on the personality of teacher and student; and extrinsic barrier mainly results from the inadequate and or inappropriate arrangement of infrastructure. Meanwhile, the institutional barrier is specific to curriculum, policy, technology, as well as organizational sustenance in the education field. From the twelve of sixty previous studies in data resources, the obtained percentage of barriers are 38% for intrinsic, 33% for institutional, and 29% for extrinsic, respectively. It has been revealed that these domains have quite a similar percentage, but intrinsic factors came up as the most reliable barrier in STEM education.